Problems Of Agrarian Reform As A Strategy For Implementing Land Reform Plus In Indonesia - Gunawan (LEGAL BRIEF, 2022)
The Agrarian Reform as a strategy for implementing land reform plus as regulated in the Decree of the People's Consultative Assembly of the Republic of Indonesia Number IX/MPR/2001 concerning Agrarian Reform and Natural Resource Management, and Law Number 17 of 2007 concerning the National Long-Term Development Plan for 2005-2025 and Presidential Regulation Number 86 of 2018 concerning Agrarian Reform as the implementing regulation of Agrarian Reform in order to improve social justice and people's welfare in the acquisition and use of agricultural land as an effort to improve the welfare of the community, especially farmers in Indonesia. The spirit and strong commitment to fight for agrarian reform does not mean that it will eliminate the challenges, obstacles, and obstacles in the implementation of agrarian reform. Usually, problems will always be encountered in the implementation of an activity, including the implementation of agrarian reform as a strategy for implementing land reform plus in Indonesia. Based on these problems, the purpose of this study is to identify and find the problems of agrarian reform as a strategy for implementing land reform plus in Indonesia, and solving the problems of agrarian reform as a strategy for implementing land reform plus in Indonesia.